Building up local productivity: Infrastructure and firm dynamics in Mexico - Matias Busso; Oscar Fentanes (Inter-American Development Bank (IDB), 2024)
What determines the aggregate and distributional effects of new transportation infrastructure? One key overlooked channel is the role that infrastructure policy plays in changing the incentives of firms to enter, exit, and grow–in turn generating endogenous changes in local productivity. In this paper, we document and quantify the importance of this channel by using detailed Mexican microdata and a spatial general-equilibrium model that incorporates firm dynamics. Leveraging random delays in the construction of highways, we empirically show that productivity grows in places with better transportation infrastructure. Firms play a critical role in driving these results: highways increase firms' size, entry rates, survival rates, and total factor productivity. Then, by calibrating our model on census data between 1998 and 2018, we find that new highways over this period increased welfare and income by half a percent, similar to its costs in terms of GDP. Moreover, we find substantial spatial reallocation of workers and production. Nearly half of these effects are explained by endogenous changes in local productivity, which is driven by firm dynamics.
Keywords: R12; D24; L25; O18; O54; 330; Economic geography; firm dynamics; infrastructure